2021
DOI: 10.3390/ijerph18136952
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Introducing Successive Biosimilars on Changes in Prices of Adalimumab, Infliximab, and Trastuzumab—Polish Experiences

Abstract: Biosimilars are cheaper than original drugs and are thus of interest to the public. The aim of this article is to assess the benefits of introducing more than one biosimilar for the same substance (active pharmaceutical ingredient, API). The hypothesis is that the introduction of successive biosimilars of a specific original drug reduces the price of the selected API. The study focuses on drug prices varying with the successive arrival of new biosimilars. Three drugs that have at least three reimbursed biosimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Vogler and colleagues highlighted that the policies to encourage the use of biosimilars in European countries have clearly demonstrated potential savings [ 39 ]. Barszczewska and Piechota reported that the introduction of more biosimilars could lead to sales competition, resulting in further price reductions and potential budget savings in Poland [ 40 ]. It has been reported that Austria’s strong pricing policy for biosimilars has discouraged biosimilar competition [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vogler and colleagues highlighted that the policies to encourage the use of biosimilars in European countries have clearly demonstrated potential savings [ 39 ]. Barszczewska and Piechota reported that the introduction of more biosimilars could lead to sales competition, resulting in further price reductions and potential budget savings in Poland [ 40 ]. It has been reported that Austria’s strong pricing policy for biosimilars has discouraged biosimilar competition [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The average prices of both biosimilars and patented biologics have been observed to be decreasing across markets because of competition among manufacturers, thereby significantly improving patient access. This can also create conditions for competitiveness between reference products and biosimilars, where a subsequent reduction in the price of the biological originator is likely to occur [ 16 , 17 , 45 , 49 ]. Switching from a reference product to a biosimilar is typically due to insurance mandates, implementation of pharmacy formulary changes to reduce costs, or because the patient has relocated to a region where the current prescription is not available [ 56 , 60 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the cumulative savings resulting from biosimilar competition has been estimated to have surpassed €30 billion in 2022, which can be attributed to price reductions in the markets [ 16 ]. Additionally, the lower prices of a biosimilar could lead to a competitive domino effect in price reductions for other biosimilars [ 17 , 49 ]. This can be observed in counties like Denmark and Norway that follow a tender system for controlling drug prices [ 17 ].…”
Section: Overarching Principles and Consensus Recommendationsmentioning
confidence: 99%
“…To this aim, the implementation of regulations for biosimilars licensing is crucial to promote access to biologicals with assured quality, safety and efficacy (Rahalkar et al, 2021b;Wadhwa et al, 2022). It is worth mentioning that approval does not always indicate availability, which will depend on the commercial launch of the biosimilar, and funding decisions made by the health providers (Barszczewska and Piechota, 2021;Outterson et al, 2022), licensing is an essential requirement for accessing medicines in a country. As a consequence, the absence or delay in authorization of biosimilars may represent lack of availability of cost-effective treatments for major health problems.…”
Section: Discussionmentioning
confidence: 99%